Initial Coin Offerings: Risk or Opportunity? - Toma, Anca Mirela; Cerchiello, Paola (Frontiers in Artificial Intelligence, 2020)
Initial coin offerings (ICOs) are one of the several by-products of the cryptocurrencies world. Start-ups and existing businesses are turning to alternative sources of capital as opposed to classical channels like banks or venture capitalists. They can offer the inner value of their business by selling ‘tokens’, i.e. units of the chosen cryptocurrency, like a regular firm would do by means of an Initial Public Offering (IPO). The investors, of course, hope for an increase in the value of the token in the short term, provided a solid and valid business idea typically described by the ICO issuers in a white paper. However, fraudulent activities perpetrated by unscrupulous actors are frequent and it would be crucial to highlight in advance clear signs of illegal money raising. In this paper, we employ statistical approaches to detect what characteristics of ICOs are significantly related to fraudulent behaviour. We leverage a number of different variables like: entrepreneurial skills, Telegram chats and relative sentiment for each ICO, type of business, issuing country, team characteristics. Through logistic regression, multinomial logistic regression and text analysis, we are able to shed light on the riskiest ICOs.